Pediatric Ramsay Hunt Syndrome: Analysis of Three Cases - İmran Aydoğdu; Enes Ataç; Ziya Saltürk; Yavuz Atar; Erdi Özdemir; Yavuz Uyar; Ahmet Arslanoğlu; Güler Berkiten (Case Reports in Otolaryngology)
Ramsay Hunt syndrome (RHS) is a disorder characterized by herpetic eruptions on the auricle, facial paralysis, and vestibulocochlear dysfunction and is attributed to varicella zoster virus (VZV) infection in the geniculate ganglion. Although it is a common cause of acute peripheral facial paralysis, children are not usually affected. The diagnosis is based on history and physical findings. Treatment of RHS uses a combination of high-dose corticosteroids and acyclovir. This paper presents three cases diagnosed as RHS in the pediatric age group in association with the literature review. The aim of this paper is to emphasize the importance of careful examination and early initiation of therapy in suspected cases of RHS.